THE EFFECTS OF THE PAIN ENDURED DURING DENTAL TREATMENT - Diana CERGHIZAN; Sorin POPSOR; Mircea SUCIU; Andrei KOVACS (Romanian Dental Association for Education, 2013)
It has been acknowledged for many years that human pain perception is made up of multiple dimensions, including a sensory aspect and an emotional/affective quality aspect (Price, 1988). Researchers have shown that some "pain" stimuli are associated with high levels of emotionality/affect (for example, cancer pain), whereas other "pain" stimuli can produce relatively low levels of emotional distress (for example, labour pain) (Price et al.,1987). These findings indicate that people can experience very different emotional responses to very similar levels of stimuli intensity, depending on their perception of the event (Gracely, Kwilosz, 1988). Assessment of clinical pain response requires the use of measurement scales designed to capture the different dimensions of pain perception (Logan, 1995).